2022
DOI: 10.1177/01650254221116870
|View full text |Cite
|
Sign up to set email alerts
|

Persistence on challenging tasks mediates the relationship between childhood poverty and mental health problems

Abstract: Childhood disadvantage is associated with psychological distress throughout the lifespan. Poor children are alleged to give up more often than their more privileged peers when facing challenges. Yet little research has examined the role of task persistence in poverty and mental health. We test whether poverty-related deficits in persistence contribute to the well-documented link between childhood disadvantage and mental health. We used growth curve modeling to analyze three waves (ages 9, 13, and 17) of data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Within the task performance dimension of social-emotional skills, it was found that the mental well-being of Chinese underprivileged-background students is significantly and positively related to self-control, but insignificantly associated with persistence and responsibility. The finding is in accord with some previous studies (e.g., Boals et al, 2011;de Ridder & Gillebaart, 2017;Gokalp, 2023;Kim et al, 2022;Wills et al, 2016), but inconsistent with others (e.g., Armstrong et al, 2014;Hao et al, 2022;Lakeman, 2016;Pope et al, 2018). Such an inconformity may be due to the uniqueness of Chinese underprivileged-background students.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Within the task performance dimension of social-emotional skills, it was found that the mental well-being of Chinese underprivileged-background students is significantly and positively related to self-control, but insignificantly associated with persistence and responsibility. The finding is in accord with some previous studies (e.g., Boals et al, 2011;de Ridder & Gillebaart, 2017;Gokalp, 2023;Kim et al, 2022;Wills et al, 2016), but inconsistent with others (e.g., Armstrong et al, 2014;Hao et al, 2022;Lakeman, 2016;Pope et al, 2018). Such an inconformity may be due to the uniqueness of Chinese underprivileged-background students.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, Armstrong et al (2014) revealed that individuals' persistence from middle to late childhood predicts their mental health symptoms at age 18. Moreover, it was found that task persistence exerts a robust impact on childhood poverty-worsening mental health (Hao et al, 2022). Also, research reported that responsibility is positively related with individuals' mental health, serving as an integrated and systematic role (Lakeman, 2016;Pope et al, 2018).…”
Section: Social-emotional Skills and Student Mental Well-beingmentioning
confidence: 99%
“…Even so, we should not ignore the importance of childhood poverty for mental health in adulthood, as significant effects have also been found in older adults. A possible mechanism of the link between childhood poverty and mental health are presented; persistent poverty-related challenging tasks 64 , disengagement coping strategy 65 , diminished spatial short-term memory, and helplessness behaviors 66 . Poverty is not only one of the critical social determinants of health 67 , but also an adversity that should primarily be addressed during childhood, when it has significant implications for neurodevelopment, social development, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, stress resistance may be most effective to avoid negative emotions such as anxiety, duo to its power on handling stress or other affective problems (Anglim et al, 2020;Guo et al, 2023;Kotov et al, 2010). Additionally, responsibility, persistence, self-control, attachment, self-compassion, empathy, creativity, curiosity, gratitude, hope all exert a protective impact on individuals' mental health, including promoting mental relaxation, facilitating self-expression, boosting the immune system, and reducing blood pressure and psychological stress (Appel et al, 2023;Clarke et al, 2021;Gokalp, 2023;Hao et al, 2022;Lakeman, 2016;Leckey, 2011;Macaskill & Denovan, 2014).…”
Section: Social-emotional Skills and Student Psychological Outcomesmentioning
confidence: 99%